Bundo Kanduang: A Powerful Or Powerless Ruler? Literary Analysis of Kaba Cindua Mato (Hikayat Nan Muda Tuanku Pagaruyung) - Elfira, Mina (UI Scholars Hub, 2007)
Kaba Cinduo Mato cannot be separated from Minangkabau social life, both in public and private spaces. This kaba describes the life of’ Bundo Kanduang Bundo Kanduang, believed by most of Minangkabau people as the first queen of Pagaruyung. It is believed that Bundo Kanduang established the foundation of Minangkabau government system which was based on Islamic and matrilineal principles. The legend of Bundo Kanduang, whose image has still dominated the daily life of Minangkabau women in contemporary Minangkabau society, has become the research focus of some researches who are interested in analysing gender politics within Minangkabau society. The image of Bundo Kanduang in Kaba Cinduo Mato is used in order to answer some questions such as “Who holds the power within Minangkabau society?” and “Is it possible for a woman to be a leader, both in public and private spaces, in Minangkabau adat society?”. This article analyses the image of Bundo Kanduang as described in Kaba Cinduo Mato. The main argument of this article is that Bundo Kanduang is described in Kaba Cinduo Mato as a ruler, who has a full authority in leading her government in Pagaruyuang kingdom, and a mother, who is strong and wise. Moreover, this kaba strengthens the description of Minangkabau as a matrilineal society where its women have some privileged rights and play significant roles in their community.